bahasa inggris - M. Yofi febrianto; Ekasari, Novita; Siregar, Ade Perdana (Journal of Business Studies and Management Review, 2025)
This study examines the effect of influencer marketing on purchase intention for Ventela shoes on the TikTok Shop platform, with brand image serving as a mediating variable. The rapid expansion of social media, particularly TikTok, has driven businesses to utilize influencer marketing strategies to attract consumers and enhance brand perception. This research aims to provide empirical evidence on the role of influencer marketing in shaping brand image and increasing consumers’ purchase intention. Data were collected through a questionnaire consisting of 16 statement items representing influencer marketing, brand image, and purchase intention constructs. The study population included active TikTok users who had seen Ventela shoe promotions by influencers. A total of 112 respondents were selected using a purposive sampling technique based on predetermined criteria. Data analysis involved descriptive analysis to outline respondent characteristics and inferential analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The findings reveal that influencer marketing has a positive and significant impact on both brand image and purchase intention. Additionally, brand image was confirmed to mediate the relationship between influencer marketing and purchase intention for Ventela shoes on TikTok Shop.